Problems and Prospects of Implementation the Structures of the Intellectual Electricity Networks in Ukraine to Increase the Level of Energy Security - Zaverbnyj, A.; Pushak, H. (Економічний вісник Донбасу, 2019)
The article formulates and substantiates the prospects for introducing the structures of intelligent electric power networks in Ukraine to increase the level of energy security. The problems of introducing these networks in Ukraine to improve its energy security are identified. The essence of the country's energy security, factors affecting its level are studied. The essence of the innovative energy system based on the concept of "Smart Grid" is determined. The advantages of this concept over the current in Ukraine today are given. The article presents the latest positioning of Ukraine’s economic policy in the energy sector. A system of interconnection of stakeholders, requirements and effects in the process of the feasibility of the Smart Grid concept in the energy sector of Ukraine was built. The stages of its formation are considered. The general functional and technological ideology of the concept of the Smart Grid system and the possibility of application in Ukraine are analyzed. The need for the energy sector of Ukraine to borrow the experience of the European Union, the USA, China, and other countries in which they are accepted at the state level is successfully implemented; national concepts of development, financing of “smart” networks in the electric power industry and other sectors of the economy are successfully implemented; they have become the basis for the formation of national energy policies, programs, energy development strategies, etc.